Space exploration - Stott, Carole; Gorton, Steve (New York, N.Y. : DK Pub., 2004)
Describes rockets, exploratory vehicles, and other technological aspects of space exploration, satellites, space stations, and the life and work of astronauts.
Dreams of space -- What is space? -- Space nations -- Rocket science -- Reusable rocket -- Race for space -- Space travelers -- Man on the moon -- How to be an astronaut -- Astronaut Fashion -- Living in space -- Astronauts at work -- Rest and play -- Danger and disaster -- Space stations -- Science without gravity -- Testing equipment -- Lone explorers -- In-depth investigators -- Landers and discoverers -- Crowded space -- Looking at Earth -- Looking into space -- Future in space -- Space technology on earth -- Working together -- 21st century exploration -- Did you know? -- Timeline -- Find out more -- Index.
Includes index.
8 - 12 years
Keywords: Astronautics; Outer space -- Exploration